Interactive methods in teaching visual arts (The Peerian Journal, 2024)
In the following sections of this article, we will delve deeper into the various interactive methods used in teaching visual arts, explore their advantages and practical applications in the classroom. From hands-on activities that encourage experimentation in visual arts education to technology integration that opens up new artistic possibilities, interactive teaching methods are rich in learning that fosters creativity, curiosity, and a lifelong passion for the arts and offers a dynamic approach.